A study on cement-based mixes with partial wood bottom ash replacement. Issue 1 (5th February 2020) - Nader, Vanessa; Awwad, Elie; Wakim, Jad; Haya, Lina Bou
Abstract : Solid waste management is a global concern, due to the ever-increasing quantities of waste materials. The scarcity of landfill space and economic challenges have urged researchers to utilise waste materials in construction as a potential solution. One such waste material is wood bottom ash that is collected from residential fireplaces. In this study, wood ash (WA) partially replaces cement and sand to produce a controlled low-strength concrete and save raw material and natural resource depletion. The chemical composition properties of WA are determined. The current research considers the effect of WA, varying from 0 to 50% by weight, on cement consistency and setting time, and fineness of cement, in addition to the concrete relative density and temperature. Additionally, the mechanical properties of mortar and concrete mixes, including WA, are investigated. Accordingly, the compressive strength, modulus of elasticity, flexural strength and splitting tensile strength are determined. Specifically, with 20% WA in concrete mixes, for tested standard cylinders at 28 d, the compressive strength, modulus of elasticity, and splitting flexure strength ranged between 10−12 MPa, 17 100−21 800 MPa and 1·2–1·8 MPa, respectively, for cement and sand replacement.